1979
DOI: 10.1002/ana.410060614
|View full text |Cite
|
Sign up to set email alerts
|

Infantile neuroaxonal dystrophy and giant axonal neuropathy: Are they related?

Abstract: Light and electron microscopic findings from two sural nerve biopsies obtained at a one-year interval from a patient with the clinical features of Seitelberger's disease are described. Ballooned axons with accumulations of membranous profiles, vesicles, mitochondria, and a homogeneous center were present, and there were masses of 90 A filaments in endothelial, endoneurial, perineurial, and Schwann cells. These pathological alterations were less prominent in the second nerve biopsy, which showed a more pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Subsequent reports indicate that GAN is neuropathy involving the central nervous system (CNS). The two cases in this paper presented signs and symptoms of CNS involvement, and also sexual precocity in case 2 Begeer et al (1979) recently reported that an increase in cytoplasmic filaments averaging 90 Ä in diameter were observed in Schwann cells, endoneurial fibroblasts, capillary endothelial cells and perineurial cells, associated with the increased number of filaments 90 Ä in diameter in some axons, in the first sural nerve biopsy of an infant with clinical features of Seitelberger's infantile neuroaxonal dystrophy. And then they also mentioned that only very few endothelial and Schwann cells showed some increase in cytoplasmic filaments, while filaments were absent in endothelial and perineurial cells, in the second sural nerve biopsy after one year from the first one.…”
Section: Discussionmentioning
confidence: 90%
“…Subsequent reports indicate that GAN is neuropathy involving the central nervous system (CNS). The two cases in this paper presented signs and symptoms of CNS involvement, and also sexual precocity in case 2 Begeer et al (1979) recently reported that an increase in cytoplasmic filaments averaging 90 Ä in diameter were observed in Schwann cells, endoneurial fibroblasts, capillary endothelial cells and perineurial cells, associated with the increased number of filaments 90 Ä in diameter in some axons, in the first sural nerve biopsy of an infant with clinical features of Seitelberger's infantile neuroaxonal dystrophy. And then they also mentioned that only very few endothelial and Schwann cells showed some increase in cytoplasmic filaments, while filaments were absent in endothelial and perineurial cells, in the second sural nerve biopsy after one year from the first one.…”
Section: Discussionmentioning
confidence: 90%